1990
DOI: 10.1159/000185980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Swimming Exercise on the Progress of Renal Dysfunction in Rat with Focal Glomerulosclerosis

Abstract: The effect of exercise on the progression of experimental renal disease was studied in adriamycin (ADR)-treated rats, a model of sclerosing glomerulonephritis with nephrotic syndrome. Two hours of daily swimming exercise was carried out for 20 weeks in ADR-treated male Lewis rats fed with either an ad libitum intake of regular chow (group 1) or a restricted amount of food (group 3), which was equal to the amount of food freely ingested by ADR-treated rats not undergoing swimming exercise (group 2). Group 3 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…This was associated with a reduc tion in proteinuria and a fall in LDL cholesterol and tri glyceride in plasma, in support of the hypothesis of an effect of plasma lipids on the progression of renal disease [14][15][16], Blood pressure apparently was not influenced by exercise training in the rats. The rat models of human renal disease were puromycin-induced nephrosis [2] or 5/ 6 nephrectomy [1], changes that might be more respon sive to the effect of exercise than e.g. adult polycystic dis ease and hypertensive nephrosclerosis which was the diag nosis in more than half of the patients in the present study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This was associated with a reduc tion in proteinuria and a fall in LDL cholesterol and tri glyceride in plasma, in support of the hypothesis of an effect of plasma lipids on the progression of renal disease [14][15][16], Blood pressure apparently was not influenced by exercise training in the rats. The rat models of human renal disease were puromycin-induced nephrosis [2] or 5/ 6 nephrectomy [1], changes that might be more respon sive to the effect of exercise than e.g. adult polycystic dis ease and hypertensive nephrosclerosis which was the diag nosis in more than half of the patients in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…Exercise in the rats was much heavier than in the patients and included 2 h of daily swimming [1,2]. This was associated with a reduc tion in proteinuria and a fall in LDL cholesterol and tri glyceride in plasma, in support of the hypothesis of an effect of plasma lipids on the progression of renal disease [14][15][16], Blood pressure apparently was not influenced by exercise training in the rats.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In an animal study, swimming was shown to alleviate hyperlipidemia and prevent progressive renal dysfunction in adriamycin-induced nephritic rats. 64 Exercise is also known to improve insulin sensitivity in skeletal muscle, and to prevent or delay the onset of type 2 DM and hypertension. 65 Additional factors Dialysis patients include individuals who have survived medical events such as malignancies, collagen disease, stroke, acute myocardial infarction, atherosclerosis, infections, 66 and drug abuse.…”
Section: Exercise Habitsmentioning
confidence: 99%
“…On the other hand, there have been few reports regarding the influence of EX on the progression of renal disease, and the results have been controversial. [21][22][23][24][25] Osato et al reported that a decrease in Scr, an increase in glomerular filtration rate, and an alleviation of glomerulosclerosis resulted from 2 h/day swimming for 20 weeks in Lewis rats. 23 Heifets et al reported an increase in glomerular filtration rate, a decrease in UP, and an alleviation of glomerulosclerosis compared with the values in sedentary rats brought about by swimming for 2 h/day for 2 months in rats with 3/4-NX.…”
Section: Discussionmentioning
confidence: 99%